2021
DOI: 10.1016/s0140-6736(21)00247-6
|View full text |Cite|
|
Sign up to set email alerts
|

The SANAD II study of the effectiveness and cost-effectiveness of levetiracetam, zonisamide, or lamotrigine for newly diagnosed focal epilepsy: an open-label, non-inferiority, multicentre, phase 4, randomised controlled trial

Abstract: Summary Background Levetiracetam and zonisamide are licensed as monotherapy for patients with focal epilepsy, but there is uncertainty as to whether they should be recommended as first-line treatments because of insufficient evidence of clinical effectiveness and cost-effectiveness. We aimed to assess the long-term clinical effectiveness and cost-effectiveness of levetiracetam and zonisamide compared with lamotrigine in people with newly diagnosed focal epilepsy. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
80
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 27 publications
(33 reference statements)
7
80
0
8
Order By: Relevance
“… 41 The SANAD II (2021) has shown that lamotrigine was superior to levetiracetam and zonisamide for time to 12-month remission and should remain the first-line treatment in patients with new-onset focal epilepsy and should be the standard treatment in future trials as an alternative to carbamazepine. 74 Kwan and Brodie also found that pregabalin has similar tolerability but seems to have inferior efficacy to lamotrigine for the treatment of new-onset focal epilepsy. 75 In patients with new-onset generalized and unclassified epilepsy, the SANAD (2007) has shown that valproate is better tolerated than topiramate and more effective than lamotrigine, 42 whereas the SANAD II (2021) has suggested that levetiracetam is inferior to valproate for time to 12-month remission.…”
Section: Principles Of Asd Selectionmentioning
confidence: 97%
See 1 more Smart Citation
“… 41 The SANAD II (2021) has shown that lamotrigine was superior to levetiracetam and zonisamide for time to 12-month remission and should remain the first-line treatment in patients with new-onset focal epilepsy and should be the standard treatment in future trials as an alternative to carbamazepine. 74 Kwan and Brodie also found that pregabalin has similar tolerability but seems to have inferior efficacy to lamotrigine for the treatment of new-onset focal epilepsy. 75 In patients with new-onset generalized and unclassified epilepsy, the SANAD (2007) has shown that valproate is better tolerated than topiramate and more effective than lamotrigine, 42 whereas the SANAD II (2021) has suggested that levetiracetam is inferior to valproate for time to 12-month remission.…”
Section: Principles Of Asd Selectionmentioning
confidence: 97%
“…Table 2 in this article presents the efficacy of ASDs against common seizure types and epilepsy syndrome. Data in Table 2 are based largely on the results of RCTs comparing the newer versus older drugs including the SANAD studies, 41 , 42 , 43 , 74 and others. 57 , 59 62 , 64 , 67 , 69 , 71 , 73 , 75 88 Table 3 and the remainder sections of this articles present guidance for ASD selection for different seizure types and epilepsy syndromes according to the 2017 ILAE classification.…”
Section: Principles Of Asd Selectionmentioning
confidence: 99%
“…Table 3 presents the efficacy of ASDs against common seizure types and epilepsy syndrome. The data supplemented in the table are based primarily on the results of RCTs comparing the newer versus older drugs, including the SANAD studies 34‐37 and others, 38‐62 and recently published meta‐analyses 63‐69 . Table 4 and the remainder sections of this article present guidance for ASD selection for the specific seizure type according to the 2017 ILAE classification of seizure types and epilepsy syndromes 14‐17 .…”
Section: Introductionmentioning
confidence: 99%
“…Focal‐onset seizures account for 60% of all epilepsies. The RCTs and meta‐analyses have demonstrated comparable efficacy of several ASDs in controlling new‐onset focal seizures 22,34,37‐44,46,58,62‐64,72,77‐83 . The drug of the first choice for “focal” and “focal to bilateral” (secondarily generalized) tonic‐clonic seizures is lamotrigine 22,34,37 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation